THE DIFFERENCES IN EMPLOYEE WORKLOAD DURING WORK FROM OFFICE AND WORK FROM HOME - Athqiya, Ais Assana; Suryani, Tatik (JURNAL EKBIS, 2024)
This research has purpose to analyze the differences in employee workload during Work From Office (WFO) and Work From Home (WFH). The ultimate goal of measuring workload is to improve working conditions, improve the design of the working environment, and the workflow streamline. Based on population 360 people staff of PT Pertamina Retail, a total of 186 samples can be obtained in this research using NASA TLX. The method of NASA TLX includes six aspecs, namely: mental demand, physical demand, temporal demand, performance, effort, and frustration level. Researcher compares the differences of workload on two working conditions WFO and WFH with Paired T Test. The significance value of the test is 0.000, meaning smaller than alpha 5%. On this basis, it can be concluded that there is a difference in workload during WFH and WFO for PT Pertamina Retail workers.